2021
DOI: 10.18805/ag.r-2165
|View full text |Cite
|
Sign up to set email alerts
|

↵Prospects of Cropping System and Nutrient Management Towards Sustainability in Agriculture: A Review

Abstract: Cropping system involves proper management of inputs in a synergistic manner. Latest advancements in cropping system has resulted in including new rewarding crops in an appropriate manner with higher efficiency in utilization of resources. This ultimately effects the farmers with higher gross returns. Considering this fact, proper cohesion of nutrients/resources is essential to maintain an optimum fertility in the soil. This involves precise integration of synthetic chemicals, organics and biofertilizers; so t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Contrary to the findings of the Department of Agriculture (DOA), which reported that 69% of the samples had medium to low levels of phosphorus, the average phosphorus content in the study area was very high (Table 9). The exact reason behind high to very high levels of phosphorus is not known, but the presence of phosphorus-containing parent materials and excessive and repeated use of manures and phosphate fertilizers may have caused the high level of phosphorus in the study area [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the findings of the Department of Agriculture (DOA), which reported that 69% of the samples had medium to low levels of phosphorus, the average phosphorus content in the study area was very high (Table 9). The exact reason behind high to very high levels of phosphorus is not known, but the presence of phosphorus-containing parent materials and excessive and repeated use of manures and phosphate fertilizers may have caused the high level of phosphorus in the study area [20,21].…”
Section: Discussionmentioning
confidence: 99%